ANALISIS FAKTOR YANG MEMPENGARUHI MINAT PESERTA DIDIK DALAM MENGIKUTI EKSTRAKURIKULER OLAHRAGA DI SMA NEGERI 1 MUARO JAMBI - Kuntum Maharani; Wawan Junresti Daya; Mohd. Adrizal (LPPM STAI Muhammadiyah Probolinggo, 2025)
The purpose of this study was to determine the more dominant factors between internal and external factors in influencing students' interest in participating in sports extracurricular activities at SMA Negeri 1 Muaro Jambi. SMA Negeri 1 Muaro Jambi is a formal school that has various extracurricular activities, there are two types of extracurricular activities, namely sports and non-sports extracurricular activities. Non-sports extracurricular activities are in great demand while sports extracurricular activities are less popular. Therefore, efforts need to be made to determine students' interests in order to improve achievement in this field. This study is a quantitative descriptive study with a survey method, where the data collection technique uses an instrument in the form of a questionnaire and is measured using a Likert scale. Based on the results of the data and conclusions in this study, the Interest of Students in Participating in Sports Extracurricular Activities at SMA Negeri 1 Muaro Jambi active status shows that external factors are the most dominant factors with a percentage of 53%, which is influenced by environmental factors. Inactive status shows that internal factors are the most dominant factors with a percentage of 64%, which is influenced by activity factors.